Causes responsible for the onset an maintenance Of the summer monsoon over India - DESAI, B. N. (MAUSAM, 1975)
Ideas put forward by Walker (1972) about the onset and maintenance of monsoon rains on the west coast of India considering validity of the hypothesis of Ramage (1966), have been discussed from the point of climatological, hydrodynamical and observational facts given in published papers, and it is shown that they are untenable. The Indian summer monsoon can be understood in the light of considerations advanced in the papers of Rao and Desai (1973 a, b).